PEMBERDAYAAN BERBASIS MASYARAKAT DALAM PEMBUATAN BATA BETON BERBAHAN DASAR METAKAOLIN DAN ABU TERBANG DI DESA LIWUTUNG DUA, KAB. MINAHASA TENGGARA - Steve Supit; Priyono Priyono; Joy Tulung (Universitas Mataram, 2023)
This community-based empowerment activity program involves SUWALA concrete brick business group partners in Liwutung Dua Village, Pasan Sub-district, Southeast Minahasa Regency with the main problem being the lack of quality of concrete brick products. To overcome this problem, empowerment activities and the application of concrete brick mix technology using local natural resources and industrial waste, namely metakaolin and fly ash, were carried out. The goal is to apply the research results to the community through the manufacture of concrete bricks based on local materials in order to improve the competitiveness and welfare of business groups and the community in general. The method used in this activity is in the form of a workshop on the technology of making concrete brick mixture and education involving business groups, village officials and students. Through this service activity, a mixture technology that produces quality concrete brick products and meets the Indonesian National Standard is obtained. However, it is still necessary to control the quality of sand used, the ratio of cement:sand mixture and the method of implementing the mixture by the trained workers. Through business management education, group members' skills in preparing financial reports increased by 80% but further guidance is still needed regarding marketing management, especially with digital technology. Expectations: It is expected that this activity can improve and increase the income of business groups and encourage improvements in the economic and social values of the community. Concrete brick products from fly ash waste and metakaolin can be a village flagship product that improves community welfare and business opportunities in Southeast Minahasa Regency.